Photodynamic and ferroptotic Ce6@ZIF-8@ssPDA for head and neck cancer treatment. (December 2022) - Wang, Miaochen; Li, Fan; Lu, Tingwei; Wu, Ruoyi; Yang, Shengbing; Chen, Wantao
Graphical abstract: Highlights: A synergistic strategy combining photodynamic and ferroptotic efficacy shows good biocompatibility and anticancer property. Responsive release of Ce6@ZIF-8@ssPDA kills Head and Neck Cancer cells intelligently. Ce6@ZIF-8@ssPDA containing disulfide bonds induces ferroptosis in a tumor microenvironment with high levels of GSH. Abstract: Nanomedicine delivery systems combined with photodynamic therapy, improve targeted cancer enrichment, reduce side effects, and enhance anticancer efficacy. Additionally, ferroptosis has emerged as a novel cancer-killing mechanism, with great potential in cancer treatment. The study aimed to treat head and neck cancers by manufacturing ZIF-8@ssPDA as a drug carrier for the chlorin e6 (Ce6) photosensitizer in response to dual stimuli of the tumor microenvironment. The ZIF-8 structure can efficiently load Ce6, and polydopamine modified with a disulfide bond (ssPDA) is evenly and densely distributed on the ZIF-8 surface. In tumor microenvironments where glutathione (GSH) concentrations are high, the ssPDA structure ruptures, directly consuming GSH and further inactivating GPX4, thereby establishing a specific anticancer effect through the ferroptosis pathway. Furthermore, the Ce6@ZIF-8 structure responsively collapses in the acidic tumor microenvironment, releasing loaded Ce6. Under the excitation of a 660-nm near-infrared laser, large singlet oxygen can be generated from released Ce6 within a short period, exerting a strong photodynamic anticancer effect. Depending on the characteristic tumor microenvironment with high GSH level and acidic environment, this dual-responsive strategy combines a photodynamic and ferroptotic effect; it might improve the treatment efficacy of head and neck cancers.